Decay resistance of acetic anhydride modified wood: a review. (1st August 2013) - Alfredsen, G; Flæte, P O; Militz, H
Abstract : Acetylation appears suited to provide adequate protection against biological attack for materials derived from non-durable wood species. But still there are unanswered questions related to resistance against fungal decay. The paper summarises existing knowledge related to fungal deterioration of acetic anhydride modified wood and also highlights future research opportunities. In addition, statistical analyses based on previously published decay fungi studies were performed to quantify what factors contribute most to the performance (calculated as test sample/control). The results showed that weight per cent gain can explain approximately 50% of the performance for acetic anhydride treated wood. Others of the applied variables, like wood species or type of fungus, can reduce the variance in performance by additional 15%. Based on the surveyed literature the degree of cell wall bulking in combination with lowering of the equilibrium moisture content seems to be the primary mode of action.